2012
DOI: 10.4269/ajtmh.2012.12-0146
|View full text |Cite
|
Sign up to set email alerts
|

Total Economic Cost and Burden of Dengue in Nicaragua: 1996–2010

Abstract: Abstract. The burden of dengue in Nicaragua has been steadily rising during the last three decades; however, there have been few efforts to quantify the burden (measured in disability-adjusted life years [DALYs]) and cost to society. Using primary data from the Nicaraguan Ministry of Health (MINSA), the total cost and burden of dengue were calculated from 1996 to 2010. Total costs included both direct costs from medical expenditures and prevention activities and indirect costs from lost productivity. The annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
(54 reference statements)
3
25
1
1
Order By: Relevance
“…However in the past decade, a trend toward infections in younger age groups (De Rivera et al, 2008; Hammond et al, 2005) and a downward shift in the age of severe dengue disease cases (Nunes-Araujo et al, 2003; Rodriguez-Barraquer et al, 2011; Teixeira et al, 2008; Teixeira et al, 2009) has been reported for the Americas. The overall burden of dengue disease in the Americas is currently estimated to be 99 – 1,300 disability adjusted life years (DALYs) per million, depending on the spatiotemporal attributes of epidemics (Guzman et al, 2010; Luz et al, 2009; Mathers et al, 2007; Torres and Castro, 2007; Wettstein et al, 2012), imposing enormous economic burdens on national economies and on patients for whom the costs associated with DENV infection significantly exceed average monthly income [(Anez et al, 2006; Armien et al, 2008; Luz et al, 2011; Shepard et al, 2011; Suaya et al, 2009; Wettstein et al, 2012) and reviewed in (Beatty et al, 2011; Gubler, 2012b)].…”
Section: Emergence and Circulation Of Dengue And Yellow Fever Virusesmentioning
confidence: 99%
“…However in the past decade, a trend toward infections in younger age groups (De Rivera et al, 2008; Hammond et al, 2005) and a downward shift in the age of severe dengue disease cases (Nunes-Araujo et al, 2003; Rodriguez-Barraquer et al, 2011; Teixeira et al, 2008; Teixeira et al, 2009) has been reported for the Americas. The overall burden of dengue disease in the Americas is currently estimated to be 99 – 1,300 disability adjusted life years (DALYs) per million, depending on the spatiotemporal attributes of epidemics (Guzman et al, 2010; Luz et al, 2009; Mathers et al, 2007; Torres and Castro, 2007; Wettstein et al, 2012), imposing enormous economic burdens on national economies and on patients for whom the costs associated with DENV infection significantly exceed average monthly income [(Anez et al, 2006; Armien et al, 2008; Luz et al, 2011; Shepard et al, 2011; Suaya et al, 2009; Wettstein et al, 2012) and reviewed in (Beatty et al, 2011; Gubler, 2012b)].…”
Section: Emergence and Circulation Of Dengue And Yellow Fever Virusesmentioning
confidence: 99%
“…The current review documents the available evidence showing that the dengue economic burden is substantial, with an estimated total annual cost ranging from US$13.5 million (in Nicaragua; in 2010 values) [21] to US$56 million (in Malaysia; in 2010 values) [19], depending on the country ( Table 1). The majority of these costs are due to hospital care and costs associated with productivity loss.…”
Section: Discussionmentioning
confidence: 98%
“…In Malaysia, Shepard et al estimated the total annual cost of dengue was US$55.83 million (in 2010 values), with 54.9 % in the public sector [19]. The estimated total annual cost of dengue varied throughout Latin America, with Panama's and Nicaragua's cost-of-illness estimates being US$16.86 million [20] (in 2006 values) and US$13.5 million [21] (in 2010 values), respectively. In Puerto Rico, the annual cost of illness (in 2010 values) was US$38.7 million, and the total cost of dengue including vector control and surveillance was US$45.65 million [22].…”
Section: Economic Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Dengue fever recognized as the most severe mosquito-borne disease, responsible for medical and economic burden together with defeat in commercial [4][5][6][7][8][9][10][11]. The World Health Organization in 2017 reported that roughly 65 to 136 million people were infected by dengue fever in every year [12].…”
Section: Introductionmentioning
confidence: 99%